Case report: A successful case of targeted immunotherapy for locally advanced pancreatic cancer under non-surgical conditions - Bi, Yuanbo; Yv, Haotian; Ma, Xiaopeng; Chen, Shengxiong (Frontiers in Immunology, 2025)
IntroductionLocally advanced pancreatic cancer (LAPC) is a borderline unresectable malignancy that presents significant treatment challenges. The management of LAPC remains a complex issue, particularly in patients who are not eligible for surgical resection.CaseHere, we report the case of a 60-year-old woman diagnosed with LAPC through pathological biopsy who subsequently underwent targeted immunotherapy following the failure of a gemcitabine, oxaliplatin, and S-1 (G&S) chemotherapy regimen.InterventionBased on next-generation sequencing (NGS), the patient’s treatment regimen was adjusted to include albumin-bound paclitaxel and capecitabine chemotherapy, along with the PD-1 inhibitor camrelizumab (200 mg/cycle) for six cycles. Throughout the treatment period, the patient consistently declined surgical intervention. Imaging studies, including an upper abdominal computed tomography (CT), revealed the formation of a calcified layer surrounding the cancerous tissue in the pancreatic head. Remarkably, the patient has shown stable disease and no evidence of metastasis since the initiation of targeted immunotherapy.ConclusionThis case highlights the potential of targeted immunotherapy for the treatment of LAPC, particularly in non-surgical patients. A personalized approach guided by NGS, combined with immunotherapy, is an effective alternative to traditional treatment strategies for managing this challenging malignancy.